Barriers and facilitators for oral health screening among tobacco users: a mixed-methods study - Abdullah Alsoghier; Abdulrahman Alnutaifi; Obaid Alotaibi; Abdulaziz Alotaibi; Abdullah Alharbi; Nada Almubarak; Sara Albassam (BMC, 2024)
Abstract Objectives Tobacco consumption adversely affects general and oral health and is considered one of the significant public health burdens globally. The present study aims to assess the barriers and facilitators for attending oral and dental health screening among tobacco users who seek cessation advice. Methodology The present mixed-methods study used group concept mapping (GCM) to identify the facilitators/barriers to attending oral health screening among young adults attending face-to-face and virtual Tobacco Cessation Clinic at King Saud University (Riyadh, Saudi Arabia) between September 2022 and April 2023. Study investigators included healthcare social workers, dental interns, and oral and maxillofacial medicinists. Information about demographics, general health, oral/dental health and tobacco use were collected using self-completed questionnaires. The barriers and facilitators were assessed following GCM by brainstorming, sorting, rating, and interpretation activities. Descriptive, multidimensional scaling and hierarchical cluster analysis were used to describe the study participants and produce concept maps of the generated statements. Results The study included 148 participants who generated 67 statements summarised into 28 statements as facilitators or barriers. Based on a 5-point importance scale, the participants indicated the importance of facilitators under health-related cluster [e.g. when I feel pain] as the highest, followed by personal [e.g. to maintain my mouth hygiene], social [e.g. the quality of treatment] and financial clusters [e.g. the reasonable cost]. Concerning barriers, financial factors [e.g. high cost] acted as the highest-rated barrier, followed by personal [e.g. lack of dental appointments] and health-related [e.g. worry that dental problems will worsen]. The social factors were the least considerable barrier [e.g. lack of time]. Clustering these facilitators/barriers on the concept map indicated their conceptual similarity by an average stress value of 0.23. Conclusion Pain was the most important facilitator to attending oral health screening by young adults seeking tobacco cessation advice. Notable barriers included the high cost of dental treatment and the lack of scheduled appointments. Thus, oral health care providers need to consider scheduling periodic and timely dental check-ups to prevent and reduce the burden of tobacco-associated and pain-causing oral diseases.